Serum immunoglobulins and biomarkers of dementia: A population‐based study. (31st December 2021) - Yaqub, Amber; Khan, Samer R.; Wolters, Frank J.; Vernooij, Meike W.; Dalm, Virgil A.S.H.; Ikram, M. Arfan; Chaker, Layal
Abstract: Background: Dementia is a complex syndrome with multiple interacting pathways leading to brain damage and ultimately the clinical manifestation. In recent years, studies have identified the immune response as a novel contributing process to the aetiology of dementia, but it remains unclear how this links to established biomarkers of dementia, for instance those measured in plasma or on neuroimaging. We studied the association of serum immunoglobulins, markers of the adaptive immune response, with biomarkers of dementia. Method: Between 1997 and 2009, serum immunoglobulins (IgA, IgG and IgM) were measured in 8, 768 participants of the population‐based Rotterdam Study (median age 62.2 years, 57.0% women). Plasma biomarkers of dementia (total tau, neurofilament light chain (NfL), amyloid‐β40 (Aβ‐40), amyloid‐β42 (Aβ‐42)) were measured in a random sample of 3, 455 participants. Neuroimaging was performed for 3, 139 participants to quantify brain volume, white matter structural integrity and markers of cerebral small vessel disease. We used linear regression models to determine cross‐sectional associations of IgA, IgG, IgM and biomarkers of dementia in plasma and on neuroimaging, while adjusting for age, sex, cohort, education, cardiovascular risk factors and stratifying for APOE ‐ε4 carriership. Plasma biomarkers were log2 transformed and neuroimaging markers were standardized to facilitate comparison. Result: Higher levels of IgA corresponded to higher log2 plasma levels of NfL (β=0.019, p=0.031), and a lower or higher tau and Aβ burden, depending on carriership of the APOE ‐ε4 allele. Higher IgM was consistent with lower levels of all plasma biomarkers, particularly among no carriers of the APOE ‐ε4 allele. No significant associations were found between IgG levels and plasma biomarkers, although associations were moderately driven by APOE ‐ε4 allele carriership. Subsequently, higher serum immunoglobulin levels and in particular IgA, generally amounted to more brain atrophy (total brain volume (β=‐0.013, p=0.032), gray matter volume (β=‐0.026, p=0.009), decreased white matter integrity and increase of cerebral small vessel disease markers (white matter hyperintensities (β=0.041, p=0.008)). Conclusion: The associations between serum immunoglobulins and biomarkers of dementia in plasma partly depend on APOE ‐ε4 carriership. Higher serum immunoglobulins generally correspond to more brain atrophy, diminished white matter integrity and more cerebral small vessel disease.